THE ROLE OF KNOWLEDGE MASTERY AND SCIENCE PROCESS SKILLS TO INCREASE THE SCIENTIFIC CREATIVITY - Zulkarnaen, Zulkarnaen; Supardi, ZA Imam; Jatmiko, Budi (Unnes Science Education Journal, 2018)
The purpose of this research is to know how big the role of mastery of knowledge and science process skills to improve scientific creativity, using C3PDR teaching model, that is teaching model that encourage and utilize knowledge mastery, science process skill, creative thinking technique and motivation to improve student's scientific creativity. The data used are the results of pre-test and post-test of: the mastery of knowledge, scientific process skills and scientific creativity, as a result of the implementation of the model conducted in the 2015/2016 learning year. The sample of this research is 160 students of 8th grade divided into 5 classes in two schools in Samarinda city. The magnitude of the role is expressed by the coefficient of determination (r2) and the probability value (p). Scores of the mastery of knowledge, scientific process skills and scientific creativity are grouped into 5 levels. Data were analyzed using Kendall Tau test b. The results showed: 1) mastery of knowledge plays a significant role to increase of scientific creativity by 30% indicated by the mode r2> 0.3 and p mode <0.0001, in the weak category, 2) the science process skills play a significant role of 20% indicated by the mode r2> 0.20 and p mode <0.0001, in the weak category. Mastery of knowledge that plays a role in scientific creativity is the mastery of knowledge more broadly and in more detail. The science process skills that plays a role in scientific creativity is of determining the variables. How the role of mastery of knowledge and skills of scientific processes in enhancing scientific creativity is discussed in this article.